2020
DOI: 10.1016/j.worlddev.2020.105063
|View full text |Cite
|
Sign up to set email alerts
|

The pandemic under siege: A view from the Gaza Strip

Abstract: In this article I argue that while the COVID-19 outbreak is at its early stages in the Gaza Strip, the Palestinian coastal enclave is particularly vulnerable to its effects – not least due to the multiplicity of existing development challenges that have resulted from an ongoing Israeli and Egyptian-imposed blockade. With the economy at a standstill, the Palestinian governing authority has limited financial resources to (re)build key sanitation, hygiene, waste treatment and water supply infrastructure. These (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…During this pandemic, people have experienced dysfunctional health systems and inefficient government responses (Okoi and Bwawa 2020 ; Shammi, Bodrud-Doza, Islam, & Rahman, 2020 ). However, the world has limited knowledge on the potential risks and impacts of the global pandemic on the refugees and displaced populations (Sen 2020 ). These populations often are forced to live with very limited resources in densely populated situations provided by either the host countries or the international aid and humanitarian agencies (Efrat 2006 ; Lau, Samari, Moresky, Casey, Kachur, Roberts, & Zard, 2020 ).…”
Section: The Global Pandemic Has Complicated the Overall Scenariomentioning
confidence: 99%
“…During this pandemic, people have experienced dysfunctional health systems and inefficient government responses (Okoi and Bwawa 2020 ; Shammi, Bodrud-Doza, Islam, & Rahman, 2020 ). However, the world has limited knowledge on the potential risks and impacts of the global pandemic on the refugees and displaced populations (Sen 2020 ). These populations often are forced to live with very limited resources in densely populated situations provided by either the host countries or the international aid and humanitarian agencies (Efrat 2006 ; Lau, Samari, Moresky, Casey, Kachur, Roberts, & Zard, 2020 ).…”
Section: The Global Pandemic Has Complicated the Overall Scenariomentioning
confidence: 99%
“…Currently, reports suggest that emergency departments in Gaza are unable to handle the strain caused by the conflict; it is an 'acute-on-chronic' issue due to the already-existing barriers in provision of trauma healthcare like shortage of medicines, oxygen, and available beds (especially intensive care units). 5,6,16 A report in March 2020 revealed that Gaza had only 70 ICU beds for its entire population, 17 revealing how the facilities are 'overstretched' even on peaceful days.…”
Section: Medical Resourcesmentioning
confidence: 99%
“…Gaza, with a population of 2 million, particularly has faced political turmoil since decades, making it a densely populated area with underdeveloped infrastructure and a desperate public health situation. 5 The recent escalation in political tension starting in the early May 2021 has exposed Gaza's inability to cope with such large-scale impairment and has been described as the worst since 2014. 6 The ensuing conflict in Gaza has resulted in a distressing humanitarian crisis while seriously hampering the effort against COVID-19 due to loss of vital healthcare infrastructure, unavailability of clean water and medical resources, and inability of the people to access medical facilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the pandemic should be viewed as a preventable biosocial injustice in its struggle for health. Another researcher (Somdeep, Sen 2020) stated that countering the impact of the pandemic would assist Gaza with its development needs without having to contend with the (political) stigma of doing so. Since the blockade generally prevents entry of travelers or foreigners, the spread of COVID-19 to Gaza's general population was minimized (Abuhabib, A.A., et al 2020).…”
mentioning
confidence: 99%